CSN COVID-19 Rapid Review Program: Management of Acute Kidney Injury. (July 2020) - Clark, Edward G.; Hiremath, Swapnil; Soroka, Steven D.; Wald, Ron; Weir, Matthew A.
Purpose: Severe acute kidney injury (AKI) is a potential complication of COVID-19-associated critical illness. This has implications for the management of COVID-19-associated AKI and the resulting increased need for kidney replacement therapy (KRT) in the intensive care unit (ICU) and elsewhere in the hospital. The Canadian Society of Nephrology COVID-19 Rapid Review Team has sought to collate and synthesize currently available resources to inform ethically justifiable decisions. The goal is the provision of the best possible care for the largest number of patients with kidney disease while considering how best to ensure the safety of the health care team. Information sources: Local, provincial, national, and international guidance and planning documents related to the COVID-19 pandemic; guidance documents available from nephrology and critical care-related professional organizations; recent journal articles and preprints related to the COVID-19 pandemic; expert opinion from nephrologists from across Canada. Methods: A working group of kidney specialist physicians was established with representation from across Canada. Kidney physician specialists met via teleconference and exchanged e-mails to refine and agree on the proposed suggestions in this document. Key findings: (1) Nephrology programs should work with ICU programs to plan for the possibility that up to 30% or more of critically ill patients with COVID-19 admitted to ICU will require kidney replacement therapy (KRT). (2) Specific suggestions pertinent to the optimal management of AKI and KRT in patients with COVID-19. These suggestions include, but are not limited to, aspects of fluid management, KRT vascular access, and KRT modality choice. (3) We describe considerations related to ensuring adequate provision of KRT, should resources become scarce during the COVID-19 pandemic. Limitations: A systematic review or meta-analysis was not conducted. Our suggestions have not been specifically evaluated in the clinical environment. The local context, including how the provision of acute KRT is organized, may impede the implementation of many suggestions. Knowledge is advancing rapidly in the area of COVID-19 and suggestions may become outdated quickly. Implications: Given that most acute KRT related to COVID-19 is likely to be required initially in the ICU setting, close collaboration and planning between critical care and nephrology programs is required. Suggestions may be updated as newer evidence becomes available.